2012
DOI: 10.1371/journal.pone.0045686
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Protein MCM3AP Is Required for Inhibition of Cellular DNA Synthesis by the IE86 Protein of Human Cytomegalovirus

Abstract: Like all DNA viruses, human cytomegalovirus (HCMV) infection is known to result in profound effects on host cell cycle. Infection of fibroblasts with HCMV is known to induce an advance in cell cycle through the G0-G1 phase and then a subsequent arrest of cell cycle in early S-phase, presumably resulting in a cellular environment optimum for high levels of viral DNA replication whilst precluding replication of cellular DNA. Although the exact mechanisms used to arrest cell cycle by HCMV are unclear, they likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Overexpression of MCM3AP inhibits DNA replication via the blockage of the S phase of cell cycle. The inhibition of cell proliferation mainly depends on the activity of MCM3AP acetylase ( Poole et al, 2012 ). MCM3AP gene is located in human chromosome 21.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MCM3AP inhibits DNA replication via the blockage of the S phase of cell cycle. The inhibition of cell proliferation mainly depends on the activity of MCM3AP acetylase ( Poole et al, 2012 ). MCM3AP gene is located in human chromosome 21.…”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms have been proposed: up-regulation of the cellular licensing inhibitor Geminin [39] and expression of the viral licensing inhibitor pUL117 [40] . In addition, a post-licensing inhibition of the MCM2-7 complex by direct physical interaction between the MCM3 acetylase MCM3AP and HCMV-IE2 has been reported [73] . Conversely, low Cyclin A2-CDK activity is known to promote, rather than constrain, MCM2-7 loading [74] – [76] , arguing against a causative role of pUL21a-Cyclin A2 interaction in the viral inhibition of pre-replicative complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably in this context, Cyclin A2 over-expression [51] as well as UL21a deletion [78] have been shown to specifically impair mRNA expression of the essential viral trans-activator and S phase inhibitor IE2 [38] , [73] . The causal chain from pUL21a via Cyclin A2 to IE2 expression and inhibition of cellular DNA synthesis was confirmed by another report by Caffarelli et al that appeared while this manuscript was in preparation [79] .…”
Section: Discussionmentioning
confidence: 99%
“…Additional reports involving the interplay between MCM proteins and HCMV lytic reactivation indicated that while the virus has no need to use the MCM complex to license viral DNA replication initiation, it conveys a clear benefit to viral DNA replication (32,(57)(58)(59). It has been speculated that deregulating the activity of host MCM proteins and limiting cellular DNA replication that competes with viral DNA replication in nuclei of infected cells provides an optimal environment for HCMV viral DNA synthesis (60,61).…”
Section: Discussionmentioning
confidence: 99%